PENGELOLAAN FASILITAS WISATA SAWAH KOTO KABUPATEN ROKAN HULU - Fedri, Al; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Sawah Koto tourist attraction in Rokan Koto Ruang Village, Rokan Hulu, offers natural attractions in the form of a wooden bridge over the rice fields and facilities such as a viewing tower, prayer room, toilets, and restaurant. However, tourist visits decreased in 2021–2023, allegedly due to suboptimal facility management. This study aims to analyze facility management and factors that influence visitor satisfaction, with a qualitative descriptive approach through observation, interviews, and documentation. The results show that the main facilities are still functioning well, but narrow road access and parking areas and the lack of directions reduce comfort. Supporting facilities such as restaurants and gazebos also require improved services. In general, management does not fully meet the principles of tourism management. Improvements in facilities and services are needed to increase visitor satisfaction and the sustainability of tourist attractions. Keywords: Facility management, Sawah Koto, tourism, Rokan Hulu.